2008
DOI: 10.1590/s0100-879x2008001200007
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against electronegative LDL inhibit atherosclerosis in LDLr-/- mice

Abstract: In order to determine the effect of antibodies against electronegative low-density lipoprotein LDL(-) on atherogenesis, five groups of LDL low receptor-deficient (LDLr-/-) mice (6 per group) were immunized with the following antibodies (100 µg each): mouse anti-LDL(-) monoclonal IgG2b, rabbit anti-LDL(-) polyclonal IgG or its Fab fragments and mouse irrelevant monoclonal IgG and non-immunized controls. Antibodies were administered intravenously one week before starting the hypercholesterolemic diet (1.25% chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 29 publications
0
18
0
6
Order By: Relevance
“…Regarding that, as the evaluation of oxidative stress in adolescents is sparsely described in the literature, this possibility needs more investigation. Grosso et al (37) evaluated the immune response to LDL(2) in mice and observed a similar profile. According to these authors, low bioavailability of antibodies to LDL(2) is correlated to generation of high immune-complex to LDL(2).…”
Section: Ratiomentioning
confidence: 84%
“…Regarding that, as the evaluation of oxidative stress in adolescents is sparsely described in the literature, this possibility needs more investigation. Grosso et al (37) evaluated the immune response to LDL(2) in mice and observed a similar profile. According to these authors, low bioavailability of antibodies to LDL(2) is correlated to generation of high immune-complex to LDL(2).…”
Section: Ratiomentioning
confidence: 84%
“…18 We previously reported that passive immunization using an anti-LDL(-) mAb in Ldlr −/− mice decreased both the cross-sectional area and the number of foam cells in atherosclerotic lesions. 19 In this study, we cloned and expressed an anti-LDL(-) 2C7 scFv in P. pastoris and determined its anti-atherogenic activity on 264.7 RAW macrophages and in LDL receptor gene knockout mice (Ldlr −/− ). Our findings reinforce the potential of novel antibody-based immunotherapeutic approaches that can lead to therapies for complex diseases such as atherosclerosis.…”
Section: Cloning and Expression Of An Anti-ldl(-) Single-chain Variabmentioning
confidence: 99%
“…The experiments were performed using an initial atherosclerotic lesion protocol as previously described. 19 All mice were fed a semisynthetic chow that was based on a Western-type diet containing 20% fat, 0.5% (w/w) cholesterol (Sigma-Aldrich), 0.5% (w/w) colic acid (Sigma-Aldrich), 16.5% casein, vitamins and minerals according to the recommendations of American Institute of Nutrition (AIN)-93. 52 All procedures were approved by the Ethics Committee for Animal Studies of the Faculty of Pharmaceutical Sciences, University of Sao Paulo in agreement with the guidelines of the Brazilian College for Animal Experimentation.…”
Section: Bacteria Strains Yeast Strains and Plasmids Escherichia Colimentioning
confidence: 99%
“…Grosso et al have reported that the passive immunization with xenogeneic polyclonal antibodies, xenogeneic Fab fragments, and allogeneic monoclonal IgG antibodies, reactive to electronegative LDL (minimally modified LDL), significantly reduced atherosclerosis in LDL-receptor-deficient mice [10].…”
Section: Vaccination Strategies Based On Epitopes Of Oxidized Ldlmentioning
confidence: 99%
“…Additional immunotherapeutic approaches have been recently evaluated with promising results [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%